Parental investment in couples who conceived spontaneously or with assisted reproductive techniques - Gameiro, S. (2011)
BACKGROUND: It has been suggested that couples who conceive with Assisted 3 Reproductive Technologies (ART) invest more in their child than couples who conceive 4 spontaneously. This study examined how parental investment in the child varied as a 5 function of method-of-conception, gender and other contextual variables, i.e. pre-natal 6 depression, social support and satisfaction with the marital relationship. METHODS: 39 7 couples who conceived with ART and 34 couples who conceived spontaneously 8 completed self-report questionnaires about depression, marital satisfaction and social 9 support at their 24th pregnancy week and about parental investment in the child 4 10 months after the partum. Data were analysed with multilevel regression analyses. 11 RESULTS: Results showed that method-of-conception and gender did not predict 12 parental investment. There was a strong association between spouses on parental 13 investment and investment was associated with couples’ satisfaction with their marital 14 relationship and the amount of support they perceived from their network. 15 CONCLUSIONS: Investment in children depends on the marital relationship and 16 support perceived from family members and friends and not on how the child was 17 conceived nor on the gender of the parents.